Flood Inundation Mapping Based on Land Use and Land Cover Change in Jatiroto Watershed, Lumajang, Indonesia - Nabilla Syafa; Agus Suharyanto; Indradi Wijatmiko (The Indonesian Institute of Science and Technology Research, 2026)
Floods are one of the most frequent natural disasters and cause considerable economic, infrastructure, and social losses, especially in areas experiencing land use/land cover change (LULC). In this study, we use GeoHECRAS and GIS to model the flood risk due to historic land use changes in the Jatiroto watershed (DAS Jatiroto) in Lumajang (East Java, Indonesia). The study evaluates the consequences of land-cover conversion between 1995 and 2023 on flood processes, including the variations of flood extent, depth, and duration. Rainfall, land use, soil types, and topography data were used to construct the flood prediction model, and the model was validated with historical flooding events. The findings indicate that the flood area is found to have increased substantially from 12.22% in 1995 to 15.66% in 2023. Moreover, flood depth was also raised, particularly in areas with urban and agricultural expansion. The research emphasizes that land-use changes play a significant role in raising the flood risk and that GeoHECRAS can simulate the flood incidences. These results can be useful for the optimization of flood disaster management and prevention in the rapidly urbanizing areas. More robust flood risk management strategies could be developed if the effects of climate change were taken into account in future studies on flood risk modeling simulations.